Tuberculosis of the pubic symphysis. (10th February 2014) - Gothwal, Sudarshan; Varshney, Peeyush; Mathur, Shivank; Songra, Bhupen
Abstract : Tuberculosis is one of India's public health problems. It involves various systems of the body, including the skeletal system. Osteoarticular tuberculosis is the second most common form of extrapulmonary tuberculosis next to lymph nodes and constitutes about 13% of all extrapulmonary cases. It is generally accepted that osteoarticular tuberculosis is the result of a haematogenous or lymphatic spread from a reactivated latent focus, usually pulmonary; however, previous infection is not always encountered, and in only 40–50% of the cases, it is possible to demonstrate another active infection site. The commonest site for skeletal tuberculosis is the spine followed by the hip, knee and ankle joints. Tuberculosis can involve literally any bone or joint. Pubic symphysis is an uncommon site for tuberculosis in the case of the skeletal system. We present a rare case of pubic symphysis tuberculosis in a 25-year-old woman presented to the general surgical department with a swelling in the right thigh region.